2018
DOI: 10.1536/ihj.17-147
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-208a Regulates H9c2 Cells Simulated Ischemia-Reperfusion Myocardial Injury via Targeting CHD9 through Notch/NF-kappa B Signal Pathways

Abstract: Ischemic reperfusion (I/R) injury is a serious problem in the treatment of ischemic heart disease. MicroRNA-208a (miR-208a) is a cardiac-specific or cardiac-enriched miRNA. This study was aimed to assess the role of miR-208a in I/R injury. H9c2 cells were used to simulate I/R injury in vitro. miR-208a expression level was measured by qPCR. H9c2 cells after simulated I/R injury were transfected with miR-208a mimic, AOS-miR-208a or negative controls. LDH release, MDA and SOD contents were measured by correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Moreover, in a myocardial infarction model, miR-150, miR-34a, and miR-130a were found to be closely related to the occurrence of myocardial I/R injury [26]. MiR-497 was shown to be downregulated in myocardial tissues after myocardial I/R injury and inhibit cardiomyocyte apoptosis [8], whereas miR-208 was found to be upregulated in H9C2 cardiomyocytes after simulated I/R injury and promote cell apoptosis [9]. These results suggest that myocardial I/R injury is closely related to abnormal miRNA expression.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, in a myocardial infarction model, miR-150, miR-34a, and miR-130a were found to be closely related to the occurrence of myocardial I/R injury [26]. MiR-497 was shown to be downregulated in myocardial tissues after myocardial I/R injury and inhibit cardiomyocyte apoptosis [8], whereas miR-208 was found to be upregulated in H9C2 cardiomyocytes after simulated I/R injury and promote cell apoptosis [9]. These results suggest that myocardial I/R injury is closely related to abnormal miRNA expression.…”
Section: Discussionmentioning
confidence: 96%
“…Increasing evidence suggests that miRNAs are associated with the occurrence and development of cardiovascular diseases by targeting different genes. For example, miR-497 was shown to suppress apoptosis and promote the proliferation of I/R-induced cardiomyocytes by targeting Mfn2 [8], while miR-208a enhanced the apoptosis of I/R-induced cardiomyocytes by targeting CHD9 [9]. Additionally, miR-378 was found to be downregulated during the hypertrophic growth of the heart and heart failure [10], while its upregulation attenuated cardiac hypertrophy and improved cardiac function by targeting MAPK1, IGF1R, GRB2, and KSR1 [11].…”
Section: Agingmentioning
confidence: 99%
“…To further investigate the underlying mechanisms of miR-208a-3p-mediated regulation of OS progression, the downstream targets of miR-208a-3p were examined. Several genes have been identified to be directly targeted by miR-208a-3p, including SFRP1, cadherin 9 and thyroid hormone receptor associated protein 1 ( 19 , 34 , 35 ). The present study verified that PTEN was a direct target of miR-208a-3p in OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that miRNAs serve a key role in a variety of biological processes, including cell proliferation, apoptosis and differentiation (2)(3)(4)(5). The abnormal expression of miRNA is associated with the development and progression of a variety of diseases including cancer, cardiovascular, metabolic, neurological and bone associated diseases (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%